Study on the coupling coordination effect and dynamic relationship between tourism development and the ecological environment: a case study of Hainan Island - Zhong, Chongqing; Wu, Xiaowei; Jia, Peihong; Zhang, Kehui (Frontiers in Ecology and Evolution, 2024)
As a Free Trade Port in China, the protection of ecological environment and high-quality tourism development on Hainan Island have become a national strategy. Exploring the coupling relationship of the two subsystems holds great practical significance for promoting the island's international demonstration area and high-quality development. Based on the characteristics of international islands, a comprehensive index system is established to explore the coupling coordination evolutionary process and interactive stress relationship of tourism development and the ecological environment in Hainan Island from 2005 to 2020. The results show: (1) From 2005 to 2019, the comprehensive evaluation index of the two subsystems of Hainan Island generally showed a continuous growth trend. (2) From 2005 to 2019, the coupling degree of the two subsystems of Hainan Island strengthened continuously, the coupling coordination degree increased steadily from a moderate imbalance to good coordination, and tourism development and the ecological environment entered a stage of parallel and benign interactive development. (3) In 2020, affected by COVID-19, the tourism development indicators declined rapidly, while the ecological environment still maintained a rising trend. (4) Based on the inverted U-shaped curve model, when the tourism development index reaches 0.7269, the ecological environment quality reaches the maximum value of 0.7956, which is the best state between the two subsystems. The ecological environment and tourism development of HainanIsland are generally in a benign interaction, but there are signs of interactive stress starting in 2017.In the future, the pressure on the ecological environment of Hainan Island will increase.